SOSIALISASI PENERAPAN KESEHATAN DAN KESELAMATAN KERJA DAN PENGENDALIAN BAHAYA DI SMKN 2 BENGKULU UTARA - Tiara Febrianti; Ferry Lismanto Syaiful (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Occupational Health and Safety (OHS) is a government policy to ensure the health and safety of workers. Based on law no. 1 of 1970 concerning Occupational Health and Safety, it is necessary to have knowledge and provisions regarding OHS to avoid the risk of work. In addition, the application of OHS is also essential to using tools, facilities, and infrastructure safely and efficiently. This activity aims to provide education and improve students' understanding of public vocational secondary schools 2 Bengkulu Utara by introducing potential hazards and hazard control as provisions and fundamental knowledge for students before carrying out internships to ensure occupational health and safety for students and minimize the occurrence of work accidents. This activity was carried out in public vocational secondary schools 2 Bengkulu Utara. This activity targets the students of public vocational secondary schools 2 Bengkulu Utara. This activity was carried out with the socialization method in the form of lectures or presentations, evaluations, and distribution of posters. The results obtained from the socialization and evaluation activities increase students' understanding and knowledge about the application of OHS in the workplace. The results obtained from the distribution of OHS posters increase students' understanding of the introduction of hazard identification and hazard control in the workplace. Based on this activity, it can be concluded that the students of public vocational secondary schools 2 Bengkulu Utara received education related to the introduction of potential hazards and hazard control and an increase in students' understanding of the application of OHS in the workplace. This activity is expected to increase students' awareness of the importance of implementing OHS.